2013
DOI: 10.11613/bm.2013.007
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunology and the influence of pro-inflammatory cytokines on osteoclasts

Abstract: Bone and immune system are functionally interconnected. Immune and bone cells derive from same progenitors in the bone marrow, they share a common microenvironment and are being influenced by similar mediators. The evidence on increased bone resorption associated with inappropriate activation of T cells such as during inflammation, is well established. However, the molecular mechanisms beyond this clinical observation have begun to be intensively studied with the advancement of osteoimmunology. Now days, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 212 publications
3
129
0
10
Order By: Relevance
“…It also contributed to 3.27% (C group), 5.42% (AN group), and 8.92% (C + AN group) of OPG/sRANKL ratio variability. These results are suggestive of a relationship between TGF-β1 and OC, OPG/sRANKL ratio in our study subjects and seem to confirm the hypothesis generated from in vitro studies, namely that TGF-β1 might play a role in the regulation of bone remodelling in girls with AN with concurrent involvement of the RANKL/RANK/OPG system [2,4,6,8]. The concept of desynchronisation between bone metabolism and the RANKL/RANK/OPG system in girls with AN seems to be lent support by a negative and significant correlation between CTx and sRANKL observed along with a positive correlation between bone markers and the OPG/sRANKL ratio.…”
Section: Prace Oryginalnesupporting
confidence: 90%
See 3 more Smart Citations
“…It also contributed to 3.27% (C group), 5.42% (AN group), and 8.92% (C + AN group) of OPG/sRANKL ratio variability. These results are suggestive of a relationship between TGF-β1 and OC, OPG/sRANKL ratio in our study subjects and seem to confirm the hypothesis generated from in vitro studies, namely that TGF-β1 might play a role in the regulation of bone remodelling in girls with AN with concurrent involvement of the RANKL/RANK/OPG system [2,4,6,8]. The concept of desynchronisation between bone metabolism and the RANKL/RANK/OPG system in girls with AN seems to be lent support by a negative and significant correlation between CTx and sRANKL observed along with a positive correlation between bone markers and the OPG/sRANKL ratio.…”
Section: Prace Oryginalnesupporting
confidence: 90%
“…Pomeroy et al [38] found significant elevation of TGF-β, while Corcos et al [39] found a significant decrease of TGF-β2, in young women with AN compared to the control participants. All these data [2,7,8,36], along with our previous results [25][26][27][28][29][30][31], indicate that the abnormal TGF-β concentrations in women with AN demonstrated by several authors [38,39] might promote the development of osteoporosis in these patients, possibly through OPG and/or RANKL. To the best of our knowledge, the relationship between potential changes in TGF-β1 concentrations and bone markers in girls with AN has not been studied so far.…”
Section: Prace Oryginalnesupporting
confidence: 61%
See 2 more Smart Citations
“…It has been shown that even a small rise in the level of systemic inflammation can precipitate osteodestruction [2,21,62].…”
Section: Effect Of Arthritic Mediators On Osteoclast Progenitorsmentioning
confidence: 99%